Pelatihan Pemasaran Digital bagi Pengusaha Laundry untuk Meningkatkan Visibilitas dan Jangkauan Pasar di Era Digital di Desa Ngimbangan - Misbachul Munir; Amelia Pristian Syah Putri; Fitri Ariani Duwi Lestari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Digital transformation brings significant changes in the way micro, small, and medium enterprises (MSMEs) carry out marketing strategies. However, many laundry business owners in rural areas, such as in Ngimbangan Village, have not optimally utilized digital marketing to improve competitiveness. This community service activity aims to increase the digital capacity of laundry business owners through digital marketing training, in order to increase business visibility and expand market reach. This activity adopts a Participatory Action Research (PAR) approach, which involves collaboration between researchers and community members at every stage of the research process, from planning to implementation and evaluation. The implementation method includes counseling, practical training, and mentoring on the use of social media, creation of promotional content, and utilization of digital platforms. The digital marketing training activities held to increase the turnover of MSMEs digital marketing training for laundry business owners to increase visibility and expand market reach in the digital era in Ngimbangan Village, Mojosari District, Mojokerto Regency, went smoothly according to the plan that had been set. The results of the activity showed an increase in participants' understanding and skills in implementing digital marketing strategies. In addition, some participants began to actively promote their businesses through social media. This activity proves that digital marketing training can be an effective means of local economic empowerment in facing the challenges of the digital era.